2020
DOI: 10.21203/rs.3.rs-72758/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dapsone Attenuates the Severity of Gastric Erosion Induced by Ethanol; Stress; and Indomethacin in Rats: A Pharmacological Approach

Abstract: Background: Dapsone, as an antimicrobial compound, has shown strong anti-inflammatory properties in clinical and experimental studies. Inflammation in stomach mocusa produce gastric erosion. Several factors contribute to the development of gastric erosions, including corticosteroids and nonsteroidal anti-inflammatory drugs (NSAIDs), alcohol, and stress. The aim of this study, therefore, was to evaluate the effects of dapsone against gastric erosions-induced by alcohol, stress, or indomethacin in rat.Methods: G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…DAP treatment during the last 2 weeks of the experimental procedure signi cantly reduced p-IKB levels suggesting a reduced activation of NF-kB and in ammation. Previous studies have been reported the inhibitory effects of DAP on NF-kB function and the reduction of pro-in ammatory cytokines [19,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DAP treatment during the last 2 weeks of the experimental procedure signi cantly reduced p-IKB levels suggesting a reduced activation of NF-kB and in ammation. Previous studies have been reported the inhibitory effects of DAP on NF-kB function and the reduction of pro-in ammatory cytokines [19,23].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the upregulation of Nrf 2 may be useful in MS therapy due to the induction of protective enzymes and the reduction of oxidative stress. Dapsone (DAP), a diaminodiphenyl sulfone, exerts antimicrobial and anti-protozoa effects [19]. This sulfonamide related drug is one of the important medication for the treatment of leprosy in [20].…”
Section: Introductionmentioning
confidence: 99%